Mycobacteria-induced anaemia revisited: a molecular approach reveals the involvement of NRAMP1 and lipocalin-2, but not of hepcidin - Rodrigues, Pedro N. S.; Gomes, Sandro S.; Neves, João V.; Gomes-Pereira, Sandra; Correia-Neves, Margarida; Nunes-Alves, Cláudio; Stolte, Jens; Sanchez, Mayka; Appelberg, Rui; Muckenthaler, Martina; Gomes, M. Salomé (Immunobiology, 2011)
Anaemia is a frequent complication of chronic infectious diseases but the exact mechanisms by which it develops remain to be clarified. In the present work, we used a mouse model of mycobacterial infection to study molecular alterations of iron metabolism induced by infection. We show that four weeks after infection with Mycobacterium avium BALB/c mice exhibited a moderate anaemia, which was not accompanied by an increase on hepatic hepcidin mRNA expression. Instead, infected mice presented increased mRNA expression of ferroportin (Slc40a1), ceruloplasmin (Cp), hemopexin (Hpx), heme-oxygenase-1 (Hmox1) and lipocalin-2 (Lcn2). Both the anaemia and the mRNA expression changes of iron-related genes were largely absent in C.D2 mice which bear a functional allele of the Nramp1 gene. Data presented in this work suggest that anaemia due to a chronic mycobacterial infection may develop in the absence of elevated hepcidin expression, is influenced by Nramp1 and may involve lipocalin-2.
Gesehen am 19.09.2022